The involvement level of Budders in jackfruit’s grafting in Malaysia - Rosli, Roziah; Mohamed Haris, Nur Bahiah (International Organization Of Scientific Research (IOSR), 2022)
Background: Previous research found that many factors affect the success of Jackfruit’s seedling production. Among the main factors involved in successful of jackfruit’s grafting are temperature and relative humidity. However, no previous study has investigated the relationship between budder’s skill, discipline and performance on jackfruit’s production. Until recently, there is no reliable evidence to show that grafting skill and discipline of budders influence the successful rate of jackfruit’s grafting. Therefore, this study aimed to measure the involvement level and work performance of jackfruit’s budders in assuring successful in jackfruit’s grafting. Materials and Methods: The six-point Likert scale questionnaire was reviewed and pre-tested for its validity and reliability. In this research, sample of all population of 21 respondents identified and data obtained from this survey were analysed and presented with significant statistical and test statistics. Results: According to the study results, the level of softwood grafting skill, wedge grafting skill, budder’s discipline, and budder’s performance are same between all budders. Conclusion: All budders having high level of softwood grafting skill, wedge grafting skill, discipline and performance.